Report of the RTB Annual Meeting 2018 - CGIAR Research Program on Roots, Tubers and Bananas (International Potato Center, 2018)
The objectives of the RTB annual meeting were: 1) To socialize progress and next steps in program implementation, M&E, communications, gender research and scaling fund; 2) For flagship and cluster leaders to position themselves for better management and science oversight; 3) For flagship project teams to improve internal communication and collaboration plans for next year; 4) To formulate plans and mechanisms for enhancing collaboration across flagships and with other CRPs and Platforms; 5) To identify key ideas to strengthen ongoing and emerging cross-cutting work.